18.1k views
2 votes
(-4,1); perpendicular to y= -5/6x +3

User Spec
by
5.6k points

1 Answer

3 votes

Answer:

y = (6/5)x + 29/5

Explanation:

To avoid confusion please enclose the fractional exponent inside parentheses: y= -5/6x +3 => y= (-5/6)x +3

The new line is to be perpendicular to the given line (above). The slope of this new line must be the negative reciprocal of (-5/6), which is (6/5).

Usig the slope-intercept formula, we get y = mx + b, or

1 = (6/5)(-4) + b

The LCD here is 5. Multiplying all 3 terms by 5, we get:

5 = 6(-4) + 5b, or

5 = -24 + 5b, or

5b = 29

Then b = 29/5, and the desired equation is:

y = (6/5)x + 29/5

User Arafath
by
5.7k points